Duration of Symptom Relief Between Injections for AbobotulinumtoxinA (Dysport®) in Spastic Paresis and Cervical Dystonia: Comparison of Evidence From Clinical Studies - Esquenazi, Alberto; Delgado, Mauricio R.; Hauser, Robert A.; Picaut, Philippe; Foster, Keith; Lysandropoulos, Andreas; Gracies, Jean-Michel (Frontiers in Neurology, 2020)
Background: Botulinum toxin-A is a well-established treatment for adult and paediatric spastic paresis and cervical dystonia. While guidelines and approved labels indicate that treatment should not occur more frequently than every 12 weeks, studies and real-world evidence show that timing of symptom recurrence between treatments may vary. Methods: We report retreatment criteria and response duration (retreatment intervals) from four pivotal, double-blind, placebo-controlled studies with open-label extensions involving patients treated with abobotulinumtoxinA (aboBoNTA) for upper- (NCT01313299) or lower-limb (NCT01249404) spastic paresis in adults, lower-limb spastic paresis in children (NCT01249417), and cervical dystonia in adults (NCT00257660). We review results in light of recently-available preclinical data. Results: In spastic paresis, 24.0–36.9% of upper-limb patients treated with aboBoNTA and 20.1–32.0% of lower-limb patients did not require retreatment before 16 weeks. 72.8–93.8% of aboBoNTA-treated paediatric patients with lower-limb spastic paresis did not require retreatment before 16 weeks (17.7–54.0% did not require retreatment before 28 weeks). In aboBoNTA-treated patients with cervical dystonia, 72.6–81.5% did not require retreatment before 16 weeks. Conclusion: AboBoNTA, when dosed as recommended, offers symptom relief beyond 12 weeks to many patients with spastic paresis and cervical dystonia. From recently available preclinical research, the amount of active neurotoxin administered with aboBoNTA might be a factor in explaining this long duration of response.